Edukasi Kesehatan pada Populasi Kunci Tentang Pencegahan Penularan HIV/AIDS di Kota Padang - Rahma, Gusni; Yulia; Dian Paramitha Asyari (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2024)
Human immunodeficiency virus (HIV) is an infection that weakens the immune system, where the most advanced stage of this disease is Acquired Immunodeficiency Syndrome (AIDS). Based on the results of previous studies, it was found that there were 37% of HIV AIDS cases in key populations in Padang City. The dominant factors that influence the incidence of HIV/AIDS in key populations are the number of sexual partners, history of needle use and history of HIV in partners with a p-value <0.05. The purpose of this community service is to improve the knowledge and attitudes of key populations with health education about preventing HIV/AIDS transmission in Padang City. The method of this activity is in the form of providing information to key populations with leaflet media. This activity will be conducted from February to June 2024. The stages of this community service include preparation, implementation and evaluation. The results of the evaluation of this activity are in the form of an increase in good knowledge from 50% to 70% and a positive attitude from 55% to 75% so that it can be concluded that this educational activity is effective in improving the attitudes and knowledge of key populations.